2012
DOI: 10.1017/s1478951512000636
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitors and mood disturbances

Abstract: We describe the case report of a 56 year old woman with no prior psychiatric history who was diagnosed with hormone receptor positive early stage breast cancer and who developed severe mood changes after administration of anastrozole which resolved after discontinuation of treatment. Aromatase inhibitors are the preferred hormonal approach for postmenopausal women with estrogen hormone sensitive breast cancer. The third-generation agents (anastrozole, letrozole and exemestane) have been shown to be more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…However, the length of life of the SERM-treated women is about the same as that of AI-treated women (5). At this point, the regimens remain unsettled (146), and concerns have been raised regarding cardiovascular complications of AIs (8,164) and mood disturbances (116). Since decreased estrogen has been implicated in cardiovascular disease and depression, the marked effect of AIs compared with partial agonist SERMs is in keeping with present knowledge (see above).…”
Section: Aromatase Inhibitorsmentioning
confidence: 64%
“…However, the length of life of the SERM-treated women is about the same as that of AI-treated women (5). At this point, the regimens remain unsettled (146), and concerns have been raised regarding cardiovascular complications of AIs (8,164) and mood disturbances (116). Since decreased estrogen has been implicated in cardiovascular disease and depression, the marked effect of AIs compared with partial agonist SERMs is in keeping with present knowledge (see above).…”
Section: Aromatase Inhibitorsmentioning
confidence: 64%
“…Aromatase is crucial in mediating the effects of testosterone on the hippocampus, amygdala, and cortex . This specific role was used as the rationale for the small studies and case reports that demonstrated that treatment with letrozole has negative effects on cognitive and affective functions . A systematic review of relevant studies with sufficient power, on the other hand, revealed no major cognitive alternations due to aromatase inhibition .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analyses of 911 breast cancer patients treated with various AI treatments or TAM compared to control women further revealed that those treated with AI or TAM showed similar verbal learning and memory impairments ( 146 ). Treatment of breast cancer patients with the AI, An, has also been associated with memory deficiencies, especially in verbal memory, mood disturbances, somnolence, anxiety, fatigue, and hot flashes in some studies ( 14 , 147 149 ).…”
Section: Human Aromatase Studiesmentioning
confidence: 99%